Thrombus of left atrium and/or its appendage in nonvalvular atrial fibrillation: echocardiographic and laboratory risk factors, capabilities for prediction and correction - I. A. Zaigraev; I. S. Yavelov (Атеротромбоз)
The review presents data on the feasibility of using laboratory findings to predict the presence of left atrium (LA) and/or left atrial appendage (LAA) thrombus in non-valvular atrial fibrillation (NvAF). It describes the relationship between the presence of a blood clot in the LA/LAA and a blood group, certain parameters of peripheral blood, blood brain natriuretic peptide levels, homocysteine, asymmetric D-methylarginine, uric acid and D-dimer.The authors presented data of studies to show a relationship between the presence of LA/LAA trombus and individual parameters obtained during transthoracic echocardiography: left ventricular mass index, left atrial volume index, LvEF/left atrial volume index ratio, E/e' ratio, peak systolic deformity of the left atrium.The capabilities of different scales in assessing the likelihood of the presence of LA/LAA thrombus in NvAF are evaluated. insufficient information capacity of the CHADS2 and CHA2DS2-vASc scales is demonstrated. The article described attempts to improve the scales by adding other risk factors (CHA2DS2-VASc-MS, CHA2DS2VASc-AFR, CHA2DS2VASc-RAF scales, as well as the possible role of additional consideration of blood brain natriuretic peptide levels). It is shown that it is feasible to add information on the duration of NvAF paroxysm and glomerular filtration rate to the CHA2DS2-VASc scale. in addition, consideration of the presence of metabolic syndrome may be beneficial. Overall, approaches with addition of information on the duration of NvAF paroxysm and glomerular filtration rate to the CHA2DS2-VASc scale proved to be most successful.The authors presented the shortcomings of accumulated evidence base regarding the relationship between the studied parameters and the presence of LA/LAA thrombus, including a small number of examined patients, usually a retrospective character of the study, a search of LA/LAA thrombus before the planned catheter ablation or electropulse therapy. As a result, it is not known to what extent the studied predictors and scales may be applied to a wider contingent of patients with NvAF. In addition, most studies have been performed on the Asian population and it is unclear whether their results can be extrapolated to other ethnic groups. It was shown that thrombi do not disappear under pressure of anticoagulant therapy in at least one-third of patients.